2013
DOI: 10.1063/1.4812024
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding clogs: The shape of arches and their stability against vibrations

Abstract: Abstract. A distinctive feature of discrete solids is their ability to form arches. These mechanically stable structures alter the isotropy of granular packings and can arrest the motion of grains when, for example, they flow through a bottleneck. Breaking arches can be achieved by means of an external vibration, which effectively eliminates clogging. Indeed, these phenomena and procedures are quite common in industrial applications. Nevertheless, there are not rigorous, well founded criteria to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Therefore, in order to get reliable and reproducible flow rates, we decided to perturb the particles just sufficiently to prevent extended periods of clogging which thereby affect flow rates. As described by Garcimartin et al [11], the problem of clogging can effectively be eliminated by applying external vibrations. In a similar way, we use the technique of 'shaking'.…”
Section: Flow Rate Without Obstructionsmentioning
confidence: 99%
“…Therefore, in order to get reliable and reproducible flow rates, we decided to perturb the particles just sufficiently to prevent extended periods of clogging which thereby affect flow rates. As described by Garcimartin et al [11], the problem of clogging can effectively be eliminated by applying external vibrations. In a similar way, we use the technique of 'shaking'.…”
Section: Flow Rate Without Obstructionsmentioning
confidence: 99%
“…To avoid jamming, one effective way is by vibration . Janda et al observed that the discharge rate significantly increased with the vibration amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Mankoc et al concluded that vibration increased the size of the avalanches (i.e., amount of particles discharged between two continuous jams) markedly. Garcimartín et al found that larger outlet orifice sizes weakened the arches that clog due to the external vibration. Mondal and Sharma observed via simulations that, for a small ratio of orifice diameter to particle diameter, having two adjacent outlets averts the jamming caused by a single outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Pournin et al [98] obtained the function for median jamming diameter (which is the hopper opening diameter for 0.5 of jamming probability) and particle diameter by investigating the effect of friction and boundary condition, and illustrated the jamming formation comes after the concentric particle rings. To avoid jamming, vibration is one of the most effective ways [28,87,99]. Janda et al [87] presented discharge behavior with the vibration and pointed out that the discharge rate increased with the vibration amplitude significantly.…”
Section: Jamming Phenomenonmentioning
confidence: 99%
“…To avoid jamming, one effective way is by vibration [28,87,99]. Janda et al [87] observed that the discharge rate significantly increased with the vibration amplitude.…”
Section: Chaptermentioning
confidence: 99%